2000
DOI: 10.1073/pnas.100047297
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous activation of NADPH oxidase-related proton and electron currents in human neutrophils

Abstract: Generation of reactive oxygen species by the NADPH oxidase complex is an important bactericidal weapon of phagocytes. Phorbol myristate acetate (PMA) is a potent agonist for this ''respiratory burst'' in human neutrophils. Although stoichiometric H ؉ efflux occurs during the respiratory burst, efforts to stimulate voltagegated H ؉ channels by PMA in whole-cell patch-clamped phagocytes have been unsuccessful. We have used a modification of the permeabilized-patch configuration that allows control of intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
266
1
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(290 citation statements)
references
References 29 publications
(45 reference statements)
19
266
1
3
Order By: Relevance
“…In phagocytes, they are thought to enable sustained NADPH oxidase activity by compensating for the electrogenic activity of the oxidase (3)(4)(5). Stimuli that activate NADPH oxidase in human eosinophils and neutrophils and in murine osteoclasts greatly enhance the opening of proton channels in these cells studied in perforated-patch configuration (6)(7)(8)(9)(10), largely via PKC phosphorylation (11). In contrast, phorbol myristate acetate (PMA) has no clear effect on proton currents in alveolar epithelial cells that lack NADPH oxidase (6).…”
mentioning
confidence: 99%
“…In phagocytes, they are thought to enable sustained NADPH oxidase activity by compensating for the electrogenic activity of the oxidase (3)(4)(5). Stimuli that activate NADPH oxidase in human eosinophils and neutrophils and in murine osteoclasts greatly enhance the opening of proton channels in these cells studied in perforated-patch configuration (6)(7)(8)(9)(10), largely via PKC phosphorylation (11). In contrast, phorbol myristate acetate (PMA) has no clear effect on proton currents in alveolar epithelial cells that lack NADPH oxidase (6).…”
mentioning
confidence: 99%
“…Although originally thought to be part of the NADPH oxidase complex, the proton channel now appears to be a distinct protein that is, nevertheless, concomitantly regulated by PKC (DeCoursey et al, 2001a). Stimuli such as arachidonic acid and PMA, which activate the proton channels in neutrophils and eosinophils, also stimulate electron transport through the oxidase (DeCoursey et al, 2000;DeCoursey et al, 2001b;Cherny et al, 2001). Although PMAstimulated NADPH oxidase activity can be blocked with the PKCδ selective inhibitor, rottlerin, the proton conductance is insensitive to PKCδ inhibition (Bankers-Fulbright, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The NADPH oxidase and its associated proton channel are often activated by the same stimuli (DeCoursey et al, 2000;DeCoursey et al, 2001b;Cherny et al, 2001). We have previously shown that superoxide production by PMAstimulated eosinophils is inhibited by the selective PKCδ Journal of Cell Science 116 (15) Fig.…”
Section: Time (Minutes) Tm Potential (Mv)mentioning
confidence: 99%
“…Defects in any one of the enzyme subunits cause chronic granulomatous disease (CGD), a genetic disease characterized by severe and recurrent bacterial infections that were fatal in childhood before the advent of antibiotics (Stasia and Li, 2008). The oxidase is electrogenic (Henderson et al, 1987) as it translocates electrons across the plasma membrane in order to produce superoxide, and the electron currents can be measured with patch-clamp electrodes in cells with high plasma membrane oxidase activity, such as neutrophils and eosinophils (Schrenzel et al, 1998;DeCoursey et al, 2000). Unless compensated, the extrusion of the negatively charged electron will depolarize the phagocyte plasma membrane to extremely high voltages, and values of +60 mV and of up to +180 mV have been reported in intact cells (Jankowski and Grinstein, 1999) and in excised patches, respectively Petheo and Demaurex, 2005).…”
mentioning
confidence: 99%
“…Proton currents of activated phagocytes have larger amplitude, faster activation kinetics (s act ), a À40 mV lower threshold of voltage activation, and markedly slower inactivation kinetics (s tail ). The last two effects are the most obvious and require the presence of a functional oxidase, because neutrophils from CGD patients only display a À13 mV shift in activation threshold and nearly normal channel closing kinetics when stimulated with phorbol 12-myristate 13-acetate (PMA) (DeCoursey et al, 2000(DeCoursey et al, , 2001Banfi et al, 1999;Petheo et al, 2003). Hv1 channels exogenously expressed in a B cell hybridoma cell line also display a À10 mV shift in activation threshold when phosphorylated, a response that requires threonine 29 ).…”
mentioning
confidence: 99%